PAI Teachers' Strategies in Improving Students' Al-Qur'an Reading Skills - Sapria, Yusti; Abbas, Abbas (Dirasah: Jurnal Pendidikan Islam, 2025)
Research objective (1) is to determine the process of learning to read the Al-Qur'an for class VIII students at Satap Middle School, SMPN 2 Bonegunu. (2) to find out PAI teachers' strategies in improving Al-Qur'an reading for class VIII students at Satap Middle School, SMPN 2 Bonegunu. (3) to determine the supporting and inhibiting factors in improving Al-Qur'an reading for Satap Middle School students at SMPN 2 Bonegunu. This type of research is descriptive qualitative. Data collection techniques using observation, interviews and documentation methods. Data analysis techniques for data reduction, data presentation and drawing conclusions. Checking the validity of source triangulation data and technical triangulation. The results of the research show that (1) students learning to read the Al-Qur'an at One Roof Public Junior High School 2 Bonegunu, in class VIII have different levels of ability for each individual. Starting from students with a fluent, moderate level of ability and still learning hijaiyah letters, (2) PAI teacher strategies, implementing refraction strategies for reading the Al-Qur'an before PAI learning begins, grouping students, and applying classical reading and listening to the Al-Qur'an. while the methods used by PAI teachers are lectures, familiarization and practice. (3) Factors that support PAI teachers in improving the ability to read the Al-Qur'an for class VIII students are the concern of the school principal, additional time. The inhibiting factors in increasing reading of the Al-Qur'an are lack of student awareness, lack of learning media facilities, and lack of role and attention from parents.